HIRADC (Hazard, Identification, Risk Assessment and Determining Control) Analysis at PT Adhi Karya Mahata Serpong in 2025 - Ananda, Delia Zakia; Santyorini, Triana (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
ABSTRACTBackground: The importance of occupationalsafety and health in the construction sector, namely at PT Adhi Karya Mahata Serpong, is the main focus behind this research. The frequent occurrence of workplace accidents in this industry highlights the need to use the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) technique to identify risks, evaluate hazards, and select appropriate control methods. The aim of this study is to provide a comprehensive overview of the risks present and the preventive measures that can be taken.Methods: The research methodology used was descriptive qualitative. Direct field observation and in-depth interviews were used to collect data. Managers and employees of PT Adhi Karya Mahata Serpong served as informants in this study. The data collection process, which focused on worker risk assessment and hazard identification, took place from December 2024 to 2025Results: Based on the study, a number of risks were noted including chemical exposure, falling objects, and falls from height. Certain activities were deemed high-risk by the risk assessment, requiring extra attention and management. The two main suggestions to lower the risk of accidents were the use of personal protective equipment (PPE) and workplace safety training.Conclusion: The conclusion of this study confirms the importance of using the HIRADC method to improve worker safety at PT Adhi Karya Mahata Serpong. To ensure compliance with established safety procedures, it is recommended that continuous safety training programs and frequent audits be conducted.Keywords: HIRADC, work safety, PPE